2020
DOI: 10.15252/embj.2019104150
|View full text |Cite
|
Sign up to set email alerts
|

Splice‐dependent trans‐synaptic PTP δ– IL 1 RAPL 1 interaction regulates synapse formation and non‐ REM sleep

Abstract: Alternative splicing regulates trans-synaptic adhesions and synapse development, but supporting in vivo evidence is limited. PTPd, a receptor tyrosine phosphatase adhering to multiple synaptic adhesion molecules, is associated with various neuropsychiatric disorders; however, its in vivo functions remain unclear. Here, we show that PTPd is mainly present at excitatory presynaptic sites by endogenous PTPd tagging. Global PTPd deletion in mice leads to input-specific decreases in excitatory synapse development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 103 publications
(205 reference statements)
2
17
0
Order By: Relevance
“…For many genes, including those associated with learning and memory or sleep, alternative splicing generates multiple mRNA transcripts [ 47 50 ]. However, it can be difficult to determine whether the products of differential splicing seen at the transcript level are translated.…”
Section: Resultsmentioning
confidence: 99%
“…For many genes, including those associated with learning and memory or sleep, alternative splicing generates multiple mRNA transcripts [ 47 50 ]. However, it can be difficult to determine whether the products of differential splicing seen at the transcript level are translated.…”
Section: Resultsmentioning
confidence: 99%
“…10 and 11 ). PVDF membranes (Millipore) were probed with rabbit polyclonal β3-Tubulin 53 (1:20,000; Abcam, ab18207, knockout validated), sheep anti-SHANK2 31 (1:2,500; R&D Systems, AF7035), rabbit anti-GRIN2B 54 (1:1,000; Abcam, ab65783), mouse anti-PSD95 55 , 56 (1:500; NeuroMab, 75–028, knockout validated), rabbit anti-Synaptophysin 57 (1:7,500; Abcam, ab32127, knockout validated), mouse anti-GAPDH 58 (1:10,000; Novus Biologicals, NB300-328), mouse anti-Nestin 59 (1:2,500; Abcam, ab22035), rabbit anti-AKT 45 (1:1,000; Cell Signaling Technology, 9272), mouse anti p-AKT(Ser473) 45 , 60 (1:1,000; Cell Signaling Technology, 4051) and rabbit anti-APP 45 (1:500, Abcam, ab126732, knockout validated).…”
Section: Methodsmentioning
confidence: 99%
“…Together, these data challenge the model that LAR-RPTPs are master synapse organizers ( Dunah et al, 2005 ; Fukai and Yoshida, 2020 ; Han et al, 2018 ; Han et al, 2020a ; Han et al, 2020b ; Kwon et al, 2010 ; Takahashi and Craig, 2013 ; Um and Ko, 2013 ; Yim et al, 2013 ). It remains possible that LAR-RPTPs control assembly of a specific subset of synapses, which may explain why PTPδ ablation causes modest layer-specific impairments of synaptic strength ( Park et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, RNAi-mediated knockdown of LAR-RPTPs or deletion of PTPσ caused generalized loss of synapse markers and defective synaptic transmission ( Dunah et al, 2005 ; Han et al, 2018 ; Han et al, 2020a ; Han et al, 2020b ), leading to the model that LAR-RPTPs control synapse formation. Furthermore, mild synaptic and behavioral defects were observed in single gene constitutive knockouts ( Elchebly et al, 1999 ; Horn et al, 2012 ; Park et al, 2020 ; Uetani et al, 2000 ; Wallace et al, 1999 ). Contrasting the RNAi-based analyses, however, a recent study used conditional mouse gene targeting to ablate PTPδ, PTPσ, and LAR, and found no overt defects in neurotransmitter release ( Sclip and Südhof, 2020 ), thereby questioning the general role of LAR-RPTPs in synapse assembly.…”
Section: Introductionmentioning
confidence: 99%